Hormonal variation in gravid does after oral treatment with crude ethanol extract of spondias mombin (2013)
Twelve mixed breed gravid rabbits weighing between 4.5-6.0kg body weights were randomly selected to study the effect of oral treatment with leaf ethanol crude extract of Spondias mombin on sex steroid hormones. Six were administered 800mg/kg of the extract while six were administered distilled water once every day for 7 days at day 14 of gestation. Blood samples were collected before commencement of treatment and 7 days post treatment in both groups. This was repeated 24 hours after parturition in the control group only. Sera from blood samples were analyzed for sex hormones concentration using ELISA. Results revealed that mean progesterone concentration significantly increased in the treatment group from pre-treatment value of 5.4±0.30ng/ml to post treatment value of 9.5±0.30ng/ml compared to significant decrease from 5.1±0.20ng/ml to 2.5±0.50ng/ml in the control group (P<0.05). All other hormones had no significant changes in both groups comparing pre and post treatment except FSH which significantly reduced from 3.1±0.08mIU/ml to 2.2±0.10mIU/ml in control group. Abortion was observed in the treatment group on days 22 and 23 of gestation, between 24 and 48 hours post treatment while all the rabbits in control group kindled a mean value of 5.7±0.68 kits at a mean gestation period of 30.3±0.33days. The study concluded that crude ethanol extract of Spondias mombin has abortifacient tendency by manipulation of steroids important in gestation.